Utilization of the Surrounding Environment as a Science Learning Resource in Gorontalo Province - Gamar Abdullah (Postgraduate, University of Mataram, 2024)
Environment-based learning is an approach that is gaining increasing attention in science education due to its potential to improve students' understanding of scientific concepts as well as practical skills. This research aims to examine in depth the utilisation of the surrounding environment of Gorontalo Province as a science learning resource, identify specific potentials that can be integrated into the curriculum and evaluate its impact on students' conceptual understanding, learning interest and practical skills. This study adopted a mixed method approach by combining experimental and interview methods to explore the utilisation of the surrounding environment as a science learning resource in Gorontalo. The population in this study were primary school students and science teachers in Gorontalo. The sample for the experimental method consisted of several elementary school classes selected by purposive sampling, quantitative data were collected through pre-test and post-test to measure changes in students' science understanding and skills before and after the intervention. Qualitative data, the sample consisted of science teachers selected through purposive sampling were interviewed. The results showed that students who participated in learning activities outside the classroom had a deeper understanding of concepts and better science skills compared to the control group. They also showed significant improvements in observation, problem-solving and co-operation skills. The out-of-class activities provided a more interactive and contextualised experience, which had a positive impact on students' motivation and interest in learning. The findings indicate that a neighbourhood-based learning approach, particularly through out-of-class learning activities, can be an effective method in improving the quality of education.